ANALISIS INDUSTRI KECIL DAN MENENGAH (IKM) SEBAGAI UPAYA MEMPERTAHANKAN KEBERLANGSUNGAN USAHA DI MASA PANDEMI COVID-19 (STUDI PADA UD. SABAR JAYA, FOLKE COFFEE, BATIPINDO JAYA, IDOLA DAN SOAK NGALAM DI KOTA MALANG) - Dista Levina A; Nasikh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of marketing costs on operating profit at NuggetSagala Rasa Kuningan Regency. The method used is descriptive verification method. Theresearch population is marketing cost data and operating profit data from 2015 to 2019,the samples are marketing cost data and Nugget Sagala Rasa operating profit data for thelast five years (2015 – 2019) which were taken using purposive sampling technique. Theresults of the simple linear regression test obtained the equation = 147,188,543,325 +4,324 X; This means that every increase in the amount of marketing costs incurred so farhas resulted in an increase in the amount of operating profit. From the results of thecorrelation test, the value of r = 0.960 means that the amount of marketing costs has avery strong relationship with the amount of operating profit. The results of thedetermination test show that the total operating profit which is influenced by the totalmarketing costs is 92.20%, while the remaining 7.80% is influenced by other factors notexamined. Based on the results of hypothesis testing using the t test, the tcount value is5.957 and ttable at a = 0.05 and dk = 3 is 2.353 so that tcount > ttable; means Ho isrejected or Ha is accepted. It can be concluded that marketing costs have a positive andsignificant effect on operating profit at Nugget Sagala Rasa, Kuningan Regency